Business Canvas Model In Business Planning (Business Canvas Model In Business Planning) - Susanto, Feri; Soleh, Ahmad; Sachanovrissa, Silke (Journal of Law, Social Science, and Management Review, 2025)
The canvas business model is a business concept that is widely used today because it is structured. The business model canvas is a business management framework created to design how the business strategy will be implemented. As the name suggests, the canvas model business is created in pictures of ideas so that everyone has the same understanding. and real about their types of consumers, costs, how the company works and so on. This research uses the literature method or library study which is research carried out by researchers using a number of literature. The business model canvas is a good method for helping business people develop their business. With correct implementation, established companies can develop and survive amidst intense competitor competition because companies can map the elements of the business circle contained in the nine elements of BMC. So with the information contained in these nine elements, companies can make policies for developing their business.